Políticas de Acesso para Discentes com Deficiência Visual no Ensino Superior: um estudo de caso. - Azevedo, Maria Carolina Albuquerque de (2012)
Far from exhausting the subject of the difficulties and facilities with which the visually deficient (SwVD) student is faced in order to enter and remain in the higher education system until the conclusion of the course, this study focuses on the discussion concerning educational and social inclusion, the public education policies designed to make educational, attitudinal and physical accessibility architectonic possible, and the influence of the use of information and communication technologies (ICT), and the effects caused by good academic performance and the achievement of moral, intellectual and economic autonomy of the blind student. Using an exploratory research of a qualitative character, we perceived that the students who received differential support in high school had better chances of entering university. In the same way, those students who received support at university have better chances of concluding their courses with quality. We trust that this dissertation has contributed to the discussion of the theme: Policies of access for students with visual deficiency to higher education: a case study , instigating the interest of the readers in continuing research on the theme.